Pengelolaan Sumber Daya Posyandu dalam Pemantauan Pertumbuhan Balita: Studi Kualitatif - Lina Rahmawati; Muhammad Zen Rahfiludin; Martha Irene Kartasurya (Journal of Bionursing, 2023)
Background. Various problems were faced by midwives at the posyandu to monitor the growth of toddlers. These problems include anthropometric measurements sometimes needing to be carried out correctly, lack of standardized anthropometric tools, lack of budget for Supplementary Feeding (PMT) for toddlers, not running the 5 tables system, and low visits to the posyandu. Objectives: This study aims to describe the barriers and solutions in managing posyandu resources by midwives to optimize the monitoring of the growth and development of toddlers. Methods. The type of research is qualitative with a case study design. Data were collected through in-depth interviews and observations from September to December 2022 at 4 health centers in Tegal Regency, with the prevalence of stunted toddlers in low (2 health centers) and high (2 health centers). In-depth interviews were conducted with 4 village midwives (primary informants) and 3 coordinating midwives (triangulation informants). Observations were conducted at 4 posyandu in the puskesmas working areas. This analysis used a thematic approach. Results. The study results showed a lack of cadres’ ability in taking anthropometric measurements correctly, the fulfilment of the posyandu budget depending on village government policies, and the distance of the posyandu. Efforts are conducting routine cadre coaching and incentives, advocacy to village government and cross-sector, and shadow posyandu. Conclusion. The study concludes that the obstacles to posyandu management can be overcome by strengthening cross-sectoral cooperation.